Sociodemographic characterization and consumption of psychoactive substances in users monitored in the therapeutic community (Research, Society and Development, 2021)
Objective: to identify the sociodemographic and psychoactive substance consumption characteristics of internal users in therapeutic communities in the interior of the Araguaia Valley, Brazil. Methodology: this is a cross-sectional survey, whose data were collected through a semi-structured questionnaire, applied to users residing in three Therapeutic Communities that welcome people in situations of drug addiction, aimed at the male audience.Results: 37 inmates were interviewed, between 19 and 70 years old, with an average of 35.5 years old, single, brown, with no monthly income, who attended elementary school and with religion. The beginning of drug use was mostly between 12 and 17 years old, with alcohol as the first drug to be used, and the reasons that led to the use were out of curiosity and to accompany friends. The family history of use was prevalent, as well as the polius of these substances, highlighting alcohol and crack as the substances that led them to dependence. The individuals had physical and mental consequences of prolonged use. Most respondents had a daily drug use before starting treatment. The search for treatment was voluntary or at the request of family members. There was a history of multiple hospitalizations, especially in the therapeutic community service. Conclusion: it is necessary to develop strategies to promote and recover the health of users who are already in problematic use of drugs, as well as the need to develop preventive actions at an earlier age among the community.